1949
DOI: 10.1111/j.1744-7348.1949.tb06398.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies in the Diagnosis of Mineral Deficiency: V. Manganese Deficiency in Wheat

Abstract: With z Text-figures)At fourteen sites where winter wheat was growing commercially, twelve of which were known or suspected to be deficient in manganese, a spray of manganese sulphate was applied late in the shooting stage of development, and the effect on yield of grain estimated. Samples of certain organs of unsprayed wheat plants were gathered on three occasions between tillering and ear emergence, and samples of weed leaves on the same occasions and after harvest ; these samples were analysed spectrographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1951
1951
1985
1985

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, with flax an important difference was noted, in that numerous minute "islands" of manganese occurred in the 'lower portions of the older leaves and stems at the normal level, whereas they were much less prevalent at the excess level. Bertrand and Rosenblatt (1922); Lyon, Beeson, and Ellis (1943 ); and Goodall (1943Goodall ( , 1949 have reported results similar to the above with respect to the existence of a gradient in manganese concentration between the older and younger leaves of plants. Jones and Bullis (1921) and Goodall (1945) have also shown that stems or petioles are much lower in manganese than the leaf lamina.…”
Section: Discussionmentioning
confidence: 60%
“…However, with flax an important difference was noted, in that numerous minute "islands" of manganese occurred in the 'lower portions of the older leaves and stems at the normal level, whereas they were much less prevalent at the excess level. Bertrand and Rosenblatt (1922); Lyon, Beeson, and Ellis (1943 ); and Goodall (1943Goodall ( , 1949 have reported results similar to the above with respect to the existence of a gradient in manganese concentration between the older and younger leaves of plants. Jones and Bullis (1921) and Goodall (1945) have also shown that stems or petioles are much lower in manganese than the leaf lamina.…”
Section: Discussionmentioning
confidence: 60%
“…Few investigators have attempted to establish a quantitative relationship between the response potentialities of plants and their chemical composition (e.g. Pfeiffer, Simmermacher, and Rippel (1919) with oats, van Itallie ( 1935) with grassland, Macy (1936) with barley, Crowther (1937) with cotton, Craig (1940) with sugar-cane, Lundegardh (1941Lundegardh ( , 1943Lundegardh ( , 1951 with oats, and Goodall (1948Goodall ( , 1949 with wheat and barley). In most of these investigations, the material for analysis was collected afteroften many months after -the treatment used to determine the response potentialities of the plants.…”
Section: Introductionmentioning
confidence: 99%
“…But very little of this work has been more than qualitative; the rapid "tissue tests" (see Nicholas 1953), for instance, have proved valuable in indicating whether plants are likely to respond to a nutrient addition during their development, but they have not been used to estimate the magnitude of these responses except in the broadest categories. It would appear that the only cases in which plant material has been analysed early enough in development for deficiencies still to be remediable, and in which the analyses could be used for quantitative forecasts of response, are in manganese deficiency of wheat (Goodall 1949) and possibly nitrogen deficiency in cotton (Crowther 1937).…”
Section: Introductionmentioning
confidence: 99%